Symbionts shape host innate immunity in honeybees. Issue 1933 (26th August 2020) - Horak, Richard D.; Leonard, Sean P.; Moran, Nancy A.
Abstract : The gut microbiome plays a critical role in the health of many animals. Honeybees are no exception, as they host a core microbiome that affects their nutrition and immune function. However, the relationship between the honeybee immune system and its gut symbionts is poorly understood. Here, we explore how the beneficial symbiont Snodgrassella alvi affects honeybee immune gene expression. We show that both live and heat-killed S. alvi protect honeybees from the opportunistic pathogen Serratia marcescens and lead to the expression of host antimicrobial peptides . Honeybee immune genes respond differently to live S. alvi compared to heat-killed S. alvi, the latter causing a more extensive immune expression response. We show a preference for Toll pathway upregulation over the Imd pathway in the presence of both live and heat-killed S. alvi . Finally, we find that live S. alvi aids in clearance of S. marcescens from the honeybee gut, supporting a potential role for the symbiont in colonization resistance. Our results show that colonization by the beneficial symbiont S. alvi triggers a replicable honeybee immune response. These responses may benefit the host and the symbiont, by helping to regulate gut microbial members and preventing overgrowth or invasion by opportunists.